Hubungan Tingkat Pengetahuan Wanita Usia Subur Tentang Kanker Serviks dengan Perilaku untuk Melakukan Pemeriksaan IVA di Desa Wonocatur - Neta Ayu Andera; Magdalena Tri Putri Apriyani (Elisabeth Health Jurnal, 2023)
Cervical cancer is the second most common cancer in women worldwide. There were more than 528,000 new cases and 266,000 deaths from cervical cancer. The main strategy to reduce deaths from cervical cancer is to perform early detection. This research is a type of Correlational Analytical research. The design used is cross sectional. The study was conducted in June 2022. The sample in this study was Women of Childbearing Age (WUS) with a total of 40 respondents. The instrument used in this research is a questionnaire. Bivariate data analysis using correlation coefficient contingency. The results showed that most of the respondents were aged 21-30 years, high school education status, work status of housewives. The data used nominal and ordinal and analyzed using the contingency coefficient test (α = 0.05).This study can be concluded that there is a significant relationship between the level of knowledge with early detection behavior. Based on these results, it is suggested that midwives can make health promotion efforts in increasing knowledge and behavior about early detection of cervical cancer.